2015
DOI: 10.1158/1055-9965.epi-15-0317
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Sex-Specific Cancers in Opposite-Sex and Same-Sex Twins in Denmark and Sweden

Abstract: Background Increasing evidence shows that some cancers originate in utero. It is hypothesized that elevated exposure to some steroid hormones might increase cancer risk and that hormone transfer between twin fetuses could result in different prenatal exposure to testosterone. Methods This large-scale prospective twin study compared opposite-sex (OS) and same-sex (SS) twins to test the impact of intrauterine exposures on cancer risk. On the basis of the Danish and Swedish twin and cancer registries, we calcul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 60 publications
3
13
0
Order By: Relevance
“…Especially OS female twins are assumed to be exposed to higher levels of testosterone in utero compared with SS females, and the effect is suggested to be larger than any possible effects of prenatal hormone transfer among OS and SS males (Cohen-Bendahan et al, 2005; Tapp et al, 2011). We did not find any significant differences between OS and SS females in any of the items of religiousness or religious coping, suggesting no evidence for the TTT hypothesis in agreement with recent studies (Ahrenfeldt, Skythe et al, 2015; Korsoff et al, 2014; Sorensen et al, 2013). On the other hand, our results could be interpreted as falsifying the TTT hypothesis.…”
Section: Discussionsupporting
confidence: 88%
“…Especially OS female twins are assumed to be exposed to higher levels of testosterone in utero compared with SS females, and the effect is suggested to be larger than any possible effects of prenatal hormone transfer among OS and SS males (Cohen-Bendahan et al, 2005; Tapp et al, 2011). We did not find any significant differences between OS and SS females in any of the items of religiousness or religious coping, suggesting no evidence for the TTT hypothesis in agreement with recent studies (Ahrenfeldt, Skythe et al, 2015; Korsoff et al, 2014; Sorensen et al, 2013). On the other hand, our results could be interpreted as falsifying the TTT hypothesis.…”
Section: Discussionsupporting
confidence: 88%
“…There are no studies of amniotic fluid testosterone levels from OS and SS twin pairs [35], and studies comparing OS with SS females have shown inconclusive results with the most consistent evidence to support the TTT hypothesis coming from studies of perception and cognition [11]. Several studies that have investigated co-twin effects in males have failed to identify differences between OS and SS male twins, for example, with regard to tooth size [36], academic performance [37], and cancer [38]. However, animal studies find that males exhibit reduced immune responses and increased intensity and prevalence of infections compared with females [4], and in humans, there is evidence that girl infants have lower mortality from infections [6] and respiratory conditions [7] compared with boys, which may reflect the immunosuppressive effects of testosterone [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Zygosity in the twin registries was determined by validated questionnaires, which are known to classify more than 95% of pairs of twins correctly (13). We restrict genetic analyses in the present study to same-sexed female twin pairs with known zygosity (9-13) as opposite-sex twin pairs require different methods and have been studied specifically in a recent study (14). The ethical committees for each country approved the study.…”
Section: Introductionmentioning
confidence: 99%